A study on the application of the student centered learning approach in the methodological axis courses of the English teaching major offered by the Foreign Language Department of the University of El Salvador during semesters I and II in the year 2018 - Alvarado Pérez, Melvin Ernesto
This descriptive research emerged from an academic change promoted by the authorities of the University of El Salvador pleading for the use of the Student Centered Learning Approach, in that sense the present study attempted to reach a better understanding if that approach is being applied or not. This research was also motivated by the information provided in the educational model which looks to improve its education.This study was placed in the School of Arts and Sciences at the Foreing Language Department specially in the Methodological Axis Courses from the English Teaching Major, during semesters I and II through the year 2018. The instruments to collect data involved observations, interviews and surveys. In addition, the results suggested that even though this approach is not entirely applied, there are many attributes of the Student Centered Learning Approach that are being applied by the professors to help the students acquire the knowledge in the Methodological Axis Courses at the Foreign Language Department. Besides, this research pretends to be a contribution to the process that the Curricular Committee of the Foreign Languages Department is carrying out in the attempt to change the current currila design.